Nursing measure in Intensive Care Unit: evidence about the Nursing Activities Score - Patrícia Cabral Ferreira; Regimar Carla Machado; Allyne Fortes Vitor; Ana Luisa Brandão de Carvalho Lira; Quênia Camille Soares Martins (Rev Rene)
his study aimed to identify the use of the Nursing Activities Score to measure the nursing workload in an Intensive Care Unit. This is a review conducted in the databases SCOPUS, CINAHL, PUBMED and LILACS in June 2013, including 18 articles that have been published since 2002. The studies included are concentrated in Brazil; the average of Nursing Activities Score was bigger than 50%, reflecting an inconsistency with the measure recommended by the Brazilian Ministry of Health. The Nursing Activities Score was the most appropriate instrument to estimate the amount of nurses in the Intensive Care Unit.; the correlation between the Nursing Activities Score and the demographic and clinical variables are not well defined in the research results, showing variations in the studies analyzed. The Nursing Activities Score is a relatively new tool, which shows a great potential for expansion due to the good results obtained with its use so far.